Myelodysplastic Syndrome in Childhood - Bilal, Hina; Naseem, Lubna; Siddiqui, Nazia (International Journal of Pathology, 2018)
Myelodysplastic syndromes (MDS) are a heterogeneous group of clonal stem cell disorders,characterized by cytopenias due to impaired blood cell production and hyper cellular and dysplasticbone marrow. The significance of MDS lies in the increased incidence of leukemic transformation.Many morphologic, immunophenotypic and genetic features observed in MDS in adults are also seenin childhood form of disease, but significant differences are reported especially in patients who do nothave increased blasts in peripheral blood or bone marrow. Here we present a case of six years female,resident of Yemen, who presented to us with suspicion of aplastic anemia but later she was diagnosedas a case of MDS.